Homocysteine Metabolism in Endothelial Cells of a Patient Homozygous for Cystathionine β-synthase (CS) Deficiency - Molen, E F van der; Hiipakka, M J; van Lith-Zanders, H; Boers, G H J; Heuvel, L P W J van den; Monnens, L A H; Blom, H J (Thrombosis and Haemostasis, 1997)
Homocystinuria due to cystathionine β-synthase (CS) deficiency is the most common inborn error of methionine metabolism. Patients with CS-deficiency have an extremely high risk of vascular disease. The underlying mechanism is still unsolved. Dysfunction of endothelial cells could be the trigger in the formation of atherosclerosis and thrombosis. Therefore, differences in cell function were studied between normal and CS-deficient human umbilical endothelial cells (HUVECs). Total homocysteine (tHcy) concentrations in culture media as a measure of homocysteine export increased in all cell lines, including the cell line with CS-deficiency, with constant amounts of approximately 2.5 μM every 24 h. von Willebrand factor (vWF), tissue plasminogen activator (tPA) and plasminogen activator inhibitor (PAI-1) in culture media were used as markers of endothelial function and increased also with progression of culture time. The effects of additions of folate, vitamin B6 and methionine to the culture medium were studied. The homocysteine export and the markers of endothelial function did not differ between the control and the CS-deficient HUVECs under various test conditions. These data show that CS-deficient endothelial cells have normal homocysteine export and normal endothelial cell function. In CS-deficient patients the very high blood levels of homocysteine, probably due to deficient CS function in liver and kidney, seems to be the hazardous factor to endothelial cells, thus promoting atherosclerosis and thrombosis in CS-deficient patients.